2021
DOI: 10.1002/pon.5840
|View full text |Cite
|
Sign up to set email alerts
|

What would I do? Perspectives on the factors underlying Lynch syndrome genetic testing and results sharing decisions for high‐risk colorectal cancer patients

Abstract: Objective Universal tumour testing for Lynch syndrome (LS) in all incident colorectal cancers (CRCs) and sequential diagnostic genetic testing is cost‐effective in Australia. Because of this, our study aimed to understand factors underlying possible decisions faced by tumour test‐positive CRC patients and their at‐risk relatives throughout the LS diagnosis pathway. Methods Semi‐structured telephone interviews were conducted with 23 participants, using four hypothetical scenarios. Vignette‐guided closed‐ and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…54,55 Many of our participants found that the process of understanding and making their decision evolved over time rather than a singular event. 18,21 Thus, preference exploration would need to be flexibly conducted as a single event or tailored to differing patient trajectories. Further, several participants experienced their prognostication decisions as stressful, and a framework for concomitant emotional support would need to be established.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…54,55 Many of our participants found that the process of understanding and making their decision evolved over time rather than a singular event. 18,21 Thus, preference exploration would need to be flexibly conducted as a single event or tailored to differing patient trajectories. Further, several participants experienced their prognostication decisions as stressful, and a framework for concomitant emotional support would need to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Many of our participants found that the process of understanding and making their decision evolved over time rather than a singular event 18,21 . Thus, preference exploration would need to be flexibly conducted as a single event or tailored to differing patient trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations